Functional Imaging and Modeling of the Heart 6th International Conference, FIMH 2011, New York City, NY, USA, May 25-27, 2011, Proceedings - Metaxas, Dimitris N.; Axel, Leon (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2011)
This book constitutes the proceedings of the 6th International Conference on Functional Imaging and Modeling of the Heart, held in New York City, NY, USA in May 2011. The 24 revised full papers presented together with 29 revised poster papers were carefully reviewed and selected from about 120 initial submissions. The contributions feature current research and development efforts in the fields of cardiovascular modeling, physiology, and image-based analysis, at a range of scales and imaging methods. Topics addresses are such as imaging, signal and image processing, applied mathematics, biomedical engineering and computer science; biologically oriented fields such as cardiac physiology and biology; as well as clinical issues such as cardiology, radiology and surgery, with a common interest in the heart.